PEMBERDAYAAN DESA BARENGKOK: MENINGKATKAN PENGELOLAAN SAMPAH ORGANIK DAN PEMANFAATAN PUPUK KOMPOS - Sukarno, Iwan; Amelia, Afifah; Indrawan, Ahsan P.; Y, Iman Nafiz.; Ramli, Moh. Agus S.; P., Rangga (Jurnal Abdi Insani, 2024)
The primary source of income for the residents of Barengkok is derived from agricultural and horticultural activities. One of the current challenges facing farmers is the persistent use of chemical fertilizers, which undoubtedly has long-term environmental consequences. The objective of this community service activity in Barengkok Village is to enhance community awareness regarding organic waste management and to provide economic and environmental benefits derived from the utilisation of compost. The activity was conducted through training in the production of organic compost, beginning with the sorting of waste materials, the preparation of the compost, and the dissemination of information regarding the benefits of compost. The methodology employed comprised several stages, including the shredding of materials, the adjustment of the carbon-to-nitrogen ratio, the fermentation of the compost with bioactivators, and the periodic turning of the compost pile. The activity was concluded with a session of socialization and training on the production of compost. It is anticipated that the results of this activity will have an impact on the community's understanding of more effective waste management practices.